Finite element analysis for crashworthiness of automotive side door reinforcement - Farhaninejad, Ali (2014)
Side impact collision is caused 40 percent serious injury during the car accident. In side impact collision, one of the most important concerns for vehicle engineers is allocating sufficient protection to automotive occupants. Although the crash zones which absorbing the energy and decreasing the magnitude of side impact force are less compared with the rear and frontal collision. However, extending the physical space between occupant and door are caused increasing the weight of vehicle. Consequently, the weight reduction of vehicle plays a crucial role to improve fuel efficiency and reducing emission gas. This factor is caused that the thin-wall structures are considered widely in vehicle industry. Side door square beam (SDSB) is one of the important parts in vehicle which plays the important role in absorbing energy of impact force and decreasing deflection. The main objective of this research is to present a practical and systematic methodology for improving the crashworthiness design of vehicle as well as obtaining the optimal design point. This research includes 2 main parts. In the first main part, the importance of side impact collision and the crashworthiness factors (SEA, PL) are investigated for side door square beam (SDSB) subjected to side impact. In the second main part, the proposed methodology is based on respond surface functions including the constrained single objective, weight and geometrical average methods. These optimization methods are employed to get the optimal design point.In this research the crashworthiness improvement and weight reduction of an SDSB are two problems which are considered. Reducing the impact force (PL) and deflection as well as increasing the specific energy absorption (SEA) are three targets which are investigated in this research. The material alloys of aluminium and steel as a reference are assigned to simple structure of SDSB to investigate the maximum SEA. It’s observed that aluminium 2011 has the maximum SEA. In addition, the effect of increasing thickness of simple structure made of aluminium 2011 is compared with reinforced structure with the same material to investigate the less deflection and maximum SEA. It’s observed that reinforced structure has the less deflection and maximum SEA compared with the simple structure. All the aforementioned comparing steps are performed by LS-DYNA software which is particularly used for finite element crash analysis. A multi-objective optimization is applied to find optimal point design to maintain maximum SEA and minimum PL for reinforced structure. Response surface methodology (RSM) is considered for design optimization in terms of single optimization and multi-objective optimization. Single –objective optimization is applied to maximize SEA while the impact force is constrained and then minimized impact force while SEA is constrained. In the second part, multiobjective optimization which include the weighted average method and geometrical average method are presented to find the optimal point of structure design. The optimization methods are solved by MATLAB software. The result shows aluminum 2011 is the light weight material to absorb more energy compared with the steel. On the other hand reinforced structure made aluminum 2011 has the less deflection. The achievement structure is optimized to find optimal design point including maximum SEA and minimum PL. The optimal design point of thicknesses is obtained 0.7 mm for the selected reinforced structure and 0.27 mm for the rib. The PL and SEA of this optimal design point is 83171 Kn and N.mm/ton respectively.